1995
DOI: 10.1136/jcp.48.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumour of lymph nodes.

Abstract: Aim-To describe the clinical, histological and immunohistochemical features in four cases of an uncommon benign lymph node lesion which may mimiic a neoplastic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…In addition, EBV was detected by in situ hybridization in one case, but only in infiltrating lymphocytes. Other reports on nodal IPT, similar lack of expression of FDC markers was described [43,45].…”
Section: Inflammatory Pseudotumor In Lymph Nodes and Spleenmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, EBV was detected by in situ hybridization in one case, but only in infiltrating lymphocytes. Other reports on nodal IPT, similar lack of expression of FDC markers was described [43,45].…”
Section: Inflammatory Pseudotumor In Lymph Nodes and Spleenmentioning
confidence: 80%
“…Proportion of spindle and inflammatory cell components varied, predominating in some areas or mostly replaced by fibrous content in others. Lesions tended to follow the vascular axis, through the hilum [16,43]. Among the cases in which an etiological agent can be detected, pathologist should search for infection, especially for T. pallidum, as it has been shown that luetic lymphadenitis may also cause lymph node IPT [18,44].…”
Section: Inflammatory Pseudotumor In Lymph Nodes and Spleenmentioning
confidence: 99%
“…In 15 to 40% of patients they are asymptomatic. When it is located in the small intestine, it generally presents as a surgical emergency [ [25] , [26] , [27] ]. In our case, the patient presented obstructive symptoms after the previously performed umbilical hernioplasty, which generated confusion since we consider that this condition was due to a complication of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies are not very specific. Imaging studies are taken for another pathology and can be found as incidental tumors, which suggest a benign process, using ultrasound and tomography, encapsulated hypodense lesions can be observed [ [25] , [26] , [27] ]. In our case, the office studies did not reveal the presence of a tumor, the diagnosis was made once the histopathological study was completed.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory myofibroblastic tumour (IMT) is a relatively rare lesion composed of a variety of inflammatory cells infiltrating in mesenchymal myofibroblastic spindle cells. [1][2][3][4] It has generally been considered a benign pseudosarcomatous disease arising from the soft tissues. It was initially described in the lung, but subsequently recognized that virtually any organ can be involved.…”
Section: Introductionmentioning
confidence: 99%